Freedom’s Frontier National Heritage Area (Symphony in the Flint Hills, 2011)
Freedom’s Frontier is a “story ecosystem.” The power of the stories does not arise from a specific place or point in time, but is formed by an understanding of how the area’s landscapes, individual stories, and perspectives were connected.
Keywords: Frontier Trails Museum; Mt. Mitchell Heritage Prairie; Sante Fe Trail; The Burnt District Monument; The Battle of Black Jack; Constitution Hall - Lecompton; Constitution Hall-Topeka